ANALISIS LOGAM (Fe, Pb), Nitrat (NO3-), DAN SULFIDA (S2-) PADA LIMBAH TAMBANG BATUBARA PT. TRI BAKTI SARIMAS DI DESA PANGKALAN KUANSING - Fadhli Kurniawan; Tengku Abu Hanifah; Subardi Bali (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
ne"> PT.Tri Bakti Sarimas (TBS) on Kuantan Singingi Regency has a great potency as liquid waste supplier in large quantity to environment as it contains hazardous heavy metals. This company has made four ponds as main water treatment facilities. Its efficiency of waste treatment installation (IPAL) could be determined by identificating the content of heavy metals (Fe and Pb), sulfide and nitrate contents at liquid waste reservoir inlet, second treatment pond, outlet and residence’s local pond. Determination of heavy metals (Fe and Pb) were done by using Atomic Absorption spectrophotometer (AAS) while UV-Vis spectrophotometer was used for sulfide and nitrate content identification. The respectively amount of Fe at inlet, second treatment pond, outlet, and residence’s local pond was 8,85 mg/L; 8,26 mg/L; 7,07 mg/L; 6,76 mg/L, respectively amount of Pb was 3,93 mg/L; 3,25 mg/L; 2,88 mg/L; 2,93 mg/L, respectively amount of sulfide (S-2 ) was 0,19 mg/L; 0,17 mg/L; 0,16 mg/L; 0,13 mg/L and respectively amount of nitrate (NO-3) was 1,23 mg/L; 0,73 mg/L; 0,51 mg/L; 0,03 mg/L. Waste water treatment in PT. TBS which has been used dolomite as adsorbent, shown the less efficiency for Fe, Pb, Sulfide and nitrate with average loss percentage less than 50 %.